Rethinking Macroeconomic Policy - Blanchard, Olivier (IMF Staff Position Notes; Staff Position Note ;, 2010)
The great moderation lulled macroeconomists and policymakers alike in the belief that we knew how to conduct macroeconomic policy. The crisis clearly forces us to question that assessment. In this paper, we review the main elements of the pre-crisis consensus, we identify where we were wrong and what tenets of the pre-crisis framework still hold, and take a tentative first pass at the contours of a new macroeconomic policy framework.